THE RELATIONSHIP BETWEEN SELF-CONTROL AND CYBERBULLYING BEHAVIOR - Dhian Sulistyowati, Arlina; Murtana, Agus; Fitria Eri Desviana, Ajeng (Universitas Airlangga, 2024)
Introduction: Self-control is an individual's ability to restrain themselves or direct themselves in a better direction with existing norms. Individuals with high self-control can control themselves well when facing various difficult situations, such as rude behavior, even aggressive behavior on social media. Cyberbullying is a negative action carried out by individuals or groups of people by sending text messages, and videos to someone's social media account to insult, embarrass, or harass the individual. Most cyberbullying perpetrators are teenagers. The increasing use of internet technology today increases the risk of cyberbullying behavior among teenagers. This study aims to determine the relationship between self-control and cyberbullying behavior in students of SMP N 2 Wedi. Method: This study uses a quantitative design with a cross-sectional and correlational approach. The sampling technique uses a proportional stratified random sampling technique with a total of 159 respondents considering the inclusion and exclusion criteria that have been determined. This study uses a self-control and cyberbullying behavior questionnaire, while data analysis uses Spearman's rank correlation. Results: The results of the study showed that students had a moderate level of self-control of 65.4% and a moderate level of cyberbullying behavior of 67.3%. The results of the data analysis showed a p-value of 0.000 <0.05 with a correlation coefficient value of -0.836. This indicates that there is a significant negative relationship between self-control and cyberbullying in female students of SMP N 2 Wedi. The higher the level of self-control, the lower the cyberbullying behavior. Conclusion: There is a relationship between self-control and cyberbullying behavior.